YouTube Kitsch and the Racial Politics of Taste in the Andes: The Case of Delfín Quishpe. - Aguiló, Ignacio (Studies in Latin American Popular Culture, 2020)
This article looks at "Torres gemelas," a YouTube video by Ecuadorian indigenous musician Delfín Quishpe, which went viral in the late 2000s, reaching millions of views. I argue that this video, and associated phenomena, can be considered a paradigmatic example of how some contemporary indigenous creators are radically redefining their relationship with globalized and localized cultures in a context of unprecedented technological change and time-space compression. By refusing to cleave to expectations about Amerindian media production as political and collective or as an expression of ancestral and traditional indigeneity, these Andean creators are challenging established views regarding how they should participate in modernity and the digital world. At the same time, white audiences' consumption of Delfín's video (and similar media products) as kitsch (or "bad taste") also points toward the deployment of racist discourse in the definition of indigenous cultural production—particularly when there is a deliberate discrepancy with mainstream society's expectations about Amerindianness. Rather than arguing against the kitsch nature of "Torres gemelas" and comparable media productions, the article proposes to critically appropriate the term in order to address how these new cultural products are subject to symbolic violence, and yet at the same time have the potential to articulate anti-racist strategies.